Analysis of Tax Disputes in Sales Transactions Involving Special Relationships in the Palm Oil Industry: A Case Study of Appeal Decisions from 2021 to 2025 - Arummalinda; Siti Nuryanah (Interdisciplinary Social Studies, 2026)
Transfer pricing disputes in related-party sales transactions remain a significant tax issue, particularly in the palm oil industry, which plays an important role in Indonesia’s economy. The complexity of determining arm’s length prices, differences in comparative data sources, and varying interpretations between taxpayers and tax authorities often lead to prolonged disputes before the Tax Court. This study aims to identify the factors causing tax disputes in sales transactions involving special relationships in the palm oil industry and to provide recommendations for minimizing similar disputes in the future. This research employed a qualitative approach using a comparative case study design. Data were obtained from 16 Tax Court appeal decisions issued between 2021 and 2025, supported by relevant regulations and semi-structured interviews with tax experts and practitioners. Data analysis was conducted using content analysis, thematic analysis, Fishbone Diagram, and the 5 Whys root cause analysis technique. The results indicate that tax disputes are primarily caused by five interconnected factors: methodology, comparative data, documentation, consistency of corrections, and regulation. The findings show that 87.5% of the analyzed decisions were fully won by taxpayers, indicating weaknesses in the evidentiary basis of tax corrections. The main root causes include the absence of a hierarchy of commodity price references, inconsistent transfer pricing methodologies, and inadequate technical guidance. This study concludes that reducing transfer pricing disputes requires improvements in regulatory certainty, audit quality, taxpayer documentation, and the development of standardized commodity price databases.